2014
DOI: 10.7150/ijms.7073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Pre-workout Supplement on Lean Mass, Muscular Performance, Subjective Workout Experience and Biomarkers of Safety

Abstract: In this prospective, randomized, double-blind, trial conducted in two parts, we examined the effects of a multi-ingredient pre-exercise workout supplement blend of creatine, betaine and a dendrobium extract (MMP) on safety, performance, and body composition in healthy men and women undergoing a supervised program of resistance exercise. Part 1 was an acute hemodynamic safety study wherein forty young, healthy men and women (26.2 ± 5.3 years, 70.4 ± 3.3 inches, 83.7 ± 14.9 kg, 26.0 ± 3.2 kg●m-2) ingest one dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 37 publications
4
25
1
5
Order By: Relevance
“…4). However, consistent with findings from Outlaw and colleagues [58], we did not observe a significant improvement in body composition changes in response to training as has previously been reported [56, 69]. This includes when adding 20 mg of synephrine (as Citrus Aurantium) to the formulation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…4). However, consistent with findings from Outlaw and colleagues [58], we did not observe a significant improvement in body composition changes in response to training as has previously been reported [56, 69]. This includes when adding 20 mg of synephrine (as Citrus Aurantium) to the formulation.…”
Section: Discussionsupporting
confidence: 92%
“…2) indicated that change in Stroop Color and Word-Color counts were significantly above baseline in the PWS group and changes in Word count, Color count, and Word-Color counts were greater in the PWS + S group after 4-weeks of training and these changes were generally greater than the placebo group. These findings are consistent with several studies that reported that acute or chronic ingestion of PWS formulations containing caffeine positively affected cognitive function, concentration, and/or perceptions of energy [5, 56, 57]. The Stroop Color-Word test assesses attention, processing speed, and executive function which have been shown to decline as one fatigues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other common ingredients include green tea extract, capsaicin and most recently raspberry ketones. Research is especially sparse with raspberry ketones with most data available coming from animal or cell culture models (Park, 2010;Morimoto et al, 2005), but recent work by Lopez (Lopez et al, 2013) and Kedia (Kedia et al, 2014) have shown positive impacts of differing multi-ingredient thermogenic supplement formulations in humans that included raspberry ketones along with other ingredients. Similar to caffeine, studies are available that have examined the sole impact of green tea extract or various catechins found in green tea on stimulating increased rates of fat oxidation and metabolic rate (Dulloo et al, 2000;Dulloo et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Os resultados demonstraram que não houve melhorias no desempenho e na composição corporal; contudo, houve melhoria significativa na sensação subjetiva de esforço (p<0,024) e na concentração (p<0,041), gerando níveis mais elevados de foco no exercício. 12 Todavia, pesquisa 13 utilizou a mesma quantidade de cafeína do estudo anterior em atletas de esportes coletivos, os quais verificaram melhora na capacidade de realização de sprints repetidos, que de acordo com Spencer e colaboradores, 14 é uma boa indicativa no desempenho em modalidades coletivas. Estes fatos relacionados à melhora da motivação e diminuição da sensação subjetiva de esforço também foram relatados em outro estudo.…”
Section: Discussionunclassified